Effect of Ca Content on Properties of Extruded Mg-3Zn-0.5Sr-xCa Alloys for Medical Applications - Zhang,Yajing (2019)
Mg-3Zn-0.5Sr-xCa(wt.%) (x=0, 0.2, 0.5) alloys were fabricated by casting and hot extrusion. X-ray diffraction (XRD) and optical microscopy observation showed that the microstructure of Mg-3Zn-0.5Sr-xCa alloys was composed of α-Mg matrix and Mg17Sr2 phase precipitated along grain boundaries. The tensile strength of the alloy increased from 255MPa to 305MPa with increasing Ca content from 0 to 0.5wt%, but the elongation to fracture of the alloys was 19.45%, 28.7% and 15.2% respectively, indicating that coarse precipitation increased the risk of crack initiation and propagation along the grain boundaries leading to reduced ductility of Mg alloys. The polarization curves revealed that Mg-3Zn-0.5Sr-0.2Ca has the highest corrosion potential and the lowest corrosion current density indicating the optimum corrosion resistance. In cytotoxicity test, Mg-3Zn-0.5Sr-xCa alloys were harmless to mouse osteoblastic and Mg-3Zn-0.5Sr-0.2Ca alloy exhibited optimal biocompatibility.